How Much New Information Is There in Earnings? - BALL, RAY; SHIVAKUMAR, LAKSHMANAN (Journal of Accounting Research, 2008)
ABSTRACT We quantify the relative importance of earnings announcements in providing new information to the share market, using the R 2 in a regression of securities' calendar‐year returns on their four quarterly earnings‐announcement “window” returns. The R 2 , which averages approximately 5% to 9%, measures the proportion of total information incorporated in share prices annually that is associated with earnings announcements. We conclude that the average quarterly announcement is associated with approximately 1% to 2% of total annual information, thus providing a modest but not overwhelming amount of incremental information to the market. The results are consistent with the view that the primary economic role of reported earnings is not to provide timely new information to the share market. By inference, that role lies elsewhere, for example, in settling debt and compensation contracts and in disciplining prior information, including more timely managerial disclosures of information originating in the firm's accounting system. The relative informativeness of earnings announcements is a concave function of size. Increased information during earnings‐announcement windows in recent years is due only in part to increased concurrent releases of management forecasts. There is no evidence of abnormal information arrival in the weeks surrounding earnings announcements. Substantial information is released in management forecasts and in analyst forecast revisions prior (but not subsequent) to earnings announcements.